The early Aptian marine stratigraphic record in the interior of Gondwana: New insights from the Araripe Basin, Northeastern Brazil - Kern, Henrique Parisi; Villegas-Martín, Jorge; Fauth, Gerson; Luft-Souza, Fernanda; Strohschoen, Oscar; Leandro, Lilian Maia; Santos, Alessandra; Bruno, Mauro Daniel Rodrigues; Tungo, Edna de Jesus Francisco; Santos Filho, Marcos Antonio Batista dos; Ceolin, Daiane; Baecker-Fauth, Simone; et al. (Elsevier, 2025)
The lower Cretaceous is marked by several episodes of global extension, such as greenhouse effects, sea level rises, oceanic anoxic events and deposition of important petroleum plays. Regarding the interior Cretaceous basins of NE South America, one of the questions to be answered is when the first marine floods occurred, how they were recorded and what their implications for the stratigraphic evolution of the sedimentary deposits. This work details the stratigraphic and paleoenvironmental evolution of Lower Cretaceous (Aptian) from the Barbalha Formation, located in the eastern portion of the Araripe Basin. For the study, six boreholes were described for obtain sedimentological, and ichnological data, and sampled to carry out petrographic (microbiofacies) and micropaleontological (calcareous and organic microfossils) analyses. Furthermore, four additional boreholes were also used for spot sampling and stratigraphic correlations. The multiproxy results allowed a new interpretation of the depositional environments and stratigraphic evolution of the two depositional sequences that make up the Barbalha Formation. The first depositional sequence comprises fluvial meandering deposits (LST1) overlain by lacustrine-lagoon deposits (TST1/HST1; equivalent to Batateira Beds). The second depositional sequence comprises alluvial plain and tidally-influenced delta deposits (LST2), overlain by bayhead delta deposits (TST2). These new interpretations are supported by microfossils (e.g., foraminifera and calcareous nannofossils) and/or marine to brackish ichnofossils that confirm marine incursions of greater or lesser magnitude throughout the analyzed interval. Finally, the preferential preservation of micropaleontological and ichnological elements in the boreholes located in the extreme east of the area studied (1PS-06-CE and 1PS-07-CE) suggests that the east-southeast region was the most affected by marine influence.
Keywords: Barbalha formation; Ichnofossils; Microfossils; Paleophysiographic evolution